2019
DOI: 10.31234/osf.io/ezawj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual objects interact differently during encoding and memory maintenance

Abstract: The storage mechanisms of working memory are the matter of an ongoing debate. The sensory recruitment hypothesis states that memory maintenance and perceptual encoding rely on the same neural substrate. This suggests that the same cortical mechanisms that shape object perception also apply to maintained memory content. We tested this prediction using the Direction Illusion, i.e., the mutual repulsion of two concurrently visible motion directions. Participants memorized the directions of two random dot patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 89 publications
0
16
0
Order By: Relevance
“…While some prior studies have used a non-target item as a reference point (e.g., Chunharas et al, 2019;Czoschke et al, 2019), several other studies have used hierarchical properties like the ensemble statistic (e.g., Brady & Alvarez, 2011) or the average color observed across all past trials (e.g., Huang & Sekuler, 2010). We note that our results could differ depending on what property the memory system uses as the reference point for repulsion bias because hierarchical properties may be automatically computed and take up space in memory independently from concurrently maintained memory items (for discussion see Brady, Konkle, & Alvarez, 2011).…”
Section: Additional Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While some prior studies have used a non-target item as a reference point (e.g., Chunharas et al, 2019;Czoschke et al, 2019), several other studies have used hierarchical properties like the ensemble statistic (e.g., Brady & Alvarez, 2011) or the average color observed across all past trials (e.g., Huang & Sekuler, 2010). We note that our results could differ depending on what property the memory system uses as the reference point for repulsion bias because hierarchical properties may be automatically computed and take up space in memory independently from concurrently maintained memory items (for discussion see Brady, Konkle, & Alvarez, 2011).…”
Section: Additional Considerationsmentioning
confidence: 99%
“…These perceptual illusions might be related to the attraction/repulsion biases observed in previous working memory studies. Previous working memory studies have used paradigms where items are encoded and tested in the same spatial location, such that working memory maintenance might have relied on retinotopically specific, sustained sensory activation (Czoschke, Peters, Rahm, Kaiser, & Bledowski, 2019). In other words, persistent neural firing in sensory areas after stimulus offset could induce visual adaptation effects similar to those observed in the aforementioned perceptual illusions.…”
Section: General Introductionmentioning
confidence: 99%
“…While some prior studies have used a non-target item as a reference point (e.g., Czoschke et al, 2019), several other studies have used hierarchical properties like the ensemble statistic (e.g., Brady & Alvarez, 2011) or the average color observed across all past trials (e.g., Huang & Sekuler, 2010). We note that our results could differ depending on what property the memory system uses as the reference point for repulsion bias because hierarchical properties may be automatically computed and take up space in memory independently from concurrently maintained memory items (for discussion see Brady, Konkle, & Alvarez, 2011).…”
Section: Additional Considerationsmentioning
confidence: 99%
“…Recent studies have revealed robust short-term influences of prior stimulation in delayed-response and working-memory tasks (Bae & Luck, 2017; Cicchini, Anobile, & Burr, 2014; Cicchini, Mikellidou, & Burr, 2018; Czoschke, Fischer, Beitner, Kaiser, & Bledowski, 2019; Czoschke, Peters, Rahm, Kaiser, & Bledowski, 2020; Fischer & Whitney, 2014; Fritsche, Mostert, & de Lange, 2017). In these studies, perceptual decision making is systematically influenced by stimulus features presented earlier in the trial (Bae & Luck, 2017; Czoschke, Fischer, Beitner, Kaiser, & Bledowski, 2019; Czoschke, Peters, Rahm, Kaiser, & Bledowski, 2020; Fritsche & de Lange, 2019; Fritsche, Mostert, & de Lange, 2017), in the previous trial (Cicchini, Mikellidou, & Burr, 2017; Cicchini, Mikellidou, & Burr, 2018; Fritsche, Mostert, & de Lange, 2017; Makovski & Jiang, 2008), or multiple trials back (Fritsche, Solomon, & De Lange, 2021; Fritsche, Spaak, & de Lange, 2020; Gekas, McDermott, & Mamassian, 2019; Suárez-Pinilla, Seth, & Roseboom, 2018). More specifically, items are reported as more similar to the task-relevant stimulus on a previous trial.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, if the attractive between-trial bias originates at the sensory processing stage, a shift in the neural representation would be expected to occur towards the target orientation on the previous trial. Based on previous research (Bae & Luck, 2020; Fischer, Czoschke, et al, 2020), we expected that between-trial biases would be modulated by the task-relevance of the item on the previous trial, such that shifts in representation would be restricted to or significantly larger for previously task-relevant items.…”
Section: Introductionmentioning
confidence: 99%